2016
DOI: 10.1007/s11010-016-2800-4
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Pnpla2 and Abhd5 and downregulation of G0s2 gene expression in mesenteric white adipose tissue as a potential reason for elevated concentration of circulating NEFA after removal of retroperitoneal, epididymal, and inguinal adipose tissue

Abstract: Elevated concentrations of circulating non-esterified fatty acids (NEFA) were reported in (a) humans with lipodystrophy, (b) humans following bariatric surgery, and (c) transgenic mice with reduced amounts of adipose tissue. Paradoxically, these findings suggest that the reduction of adipose tissue mass is associated with elevated circulating NEFA concentrations. To explain a molecular background of this phenomenon, we analyzed the effects of surgical removal of inguinal, epididymal, and retroperitoneal white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Among the 121 high genes, 47 genes (38.8%) were related with adipose tissue physiology, and 31 genes of them (66.0%) were predicted to have GC-rich transcription factor binding motifs in the promoter (Supplementary Table S8). For example, Pnpla2 is an adipose triglyceride lipase that regulates lipid metabolism in adipose tissue 1719 . A genome browsing revealed that there were five 8-oxoG peaks within the 3 kb up- or downstream of TSS of Pnpla2 gene in adipose tissues, all of which contained several GC-rich Sp1 binding sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 121 high genes, 47 genes (38.8%) were related with adipose tissue physiology, and 31 genes of them (66.0%) were predicted to have GC-rich transcription factor binding motifs in the promoter (Supplementary Table S8). For example, Pnpla2 is an adipose triglyceride lipase that regulates lipid metabolism in adipose tissue 1719 . A genome browsing revealed that there were five 8-oxoG peaks within the 3 kb up- or downstream of TSS of Pnpla2 gene in adipose tissues, all of which contained several GC-rich Sp1 binding sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the mammalian nervous system, ABHD4 was a major regulator of N -acyl phospholipid metabolism, and had the capacity to hydrolyse N -arachidonoyl phosphatidylethanolamine nape, lyso-nape, N -acyl-phospholipid serine and other N -acyl phospholipids [ 47 , 48 , 102 ]. ABHD5 could promote the decomposition of triglyceride due to its fatty triglyceride lipase activity [ 50 , 53 , 54 ]. ABHD6, which is a monoacylglycerol hydrolase, functions in balancing energy, regulating the function of brown adipose and modulating white adipose browning [ 72 ].…”
Section: Research Progress Related To the Abhd Family Membersmentioning
confidence: 99%
“…rsob.royalsocietypublishing.org Open Biol. 8: 180017 [50 -52]; activates other adipose triglyceride lipases and stimulates triglyceride breakdown as an adipose triglyceride lipase [50,53,54]; a tumour suppressor in human colorectal carcinoma development and progression [55] and serves as a novel tumour marker in sebaceous carcinoma [56]; plays an important role in protecting against atherosclerosis development in macrophages in mice [57]; tissue-specific ABHD5 deficiency leads to lipid imbalance in the liver and plasma caused by the insufficient secretion of postprandial lipoprotein [58], and upregulates gene expression related to hepatic insulin resistance, neutral lipid storage disease, fibrosis, inflammation and hepatic steatosis [59 -62]; downregulation of ABHD5 in the heart stimulates the development of diabetic cardiomyopathy by aggravating myocardial steatosis and oxidative stress [63] ABHD6 38 3p14.3 10 small intestine, spleen, duodenum as a monoacylglycerol hydrolase, involved in the activation of the endocannabinoid signalling system [44,64 -67] and systemic lupus erythematosus [68]; negatively regulates AMPAR-mediated synaptic transmission in hippocampal neurons in HEK293 T cells [69,70]; acts as a critical regulator of metabolic syndrome [71] and energy balance, including the functional realization of brown adipose and the browning of white fat by promoting glucose-stimulated insulin secretion [72]; participates in the pathogenesis of obesity and fatty liver due to its degradation functions in late endosomal/lysosomal lipid Bis [64]; a new potential diagnostic marker or an alternative therapeutic target in Ewing family tumours [ rsob.royalsocietypublishing.org Open Biol. 8: 180017…”
Section: A Regulator or Marker Of Certain Cancersmentioning
confidence: 99%
“…Similar final body weight for the controls and lipectomized rats, suggested that partial lipectomy induces a compensatory increase of adipose tissue mass located in different anatomical sites, including visceral fat. Previously, we have observed significant increase of mesenteric WAT mass after lipectomy as compared to control rats [ 44 ]. It should be noted that in normal weight women abdominal liposuction also induces increase of visceral fat [ 45 ].…”
Section: Resultsmentioning
confidence: 99%